Integrating Gemcitabine-Based Therapy With AdipoRon Enhances Growth Inhibition in Human PDAC Cell Lines - Ragone, Angela; Salzillo, Alessia; Spina, Annamaria; Naviglio, Silvio; Sapio, Luigi (Frontiers in Pharmacology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) accounts for 90% of all pancreatic cancers. Albeit its incidence does not score among the highest in cancer, PDAC prognosis is tremendously fatal. As a result of either aggressiveness or metastatic stage at diagnosis, chemotherapy constitutes the only marginally effective therapeutic approach. Despite Gemcitabine (Gem) still represents the cornerstone for PDAC management, the low response rate and the onset of resistant mechanisms claim for additional therapeutic strategies. The first synthetic orally active adiponectin receptor agonist AdipoRon (AdipoR) has recently been proposed as anticancer agent in several tumors, including PDAC. With the purpose of further addressing the AdipoR therapeutic potential, herein we investigated its pharmacodynamic interaction with Gem in human PDAC cell lines. Surprisingly, their simultaneous administration revealed a more effective action in contrasting PDAC cell growth, as well as limiting clonogenic potential, than single ones. Moreover, combination AdipoR plus Gem persisted in being effective even in Gem resistant MIA PaCa-2 cells. Whilst a different ability in braking cell cycle progression between AdipoR and Gem supported their cooperating features in PDAC, mechanistically, PD98059-mediated p44/42 MAPK ablation hindered combination effectiveness. Taken together, our findings propose AdipoR as a suitable partner in Gem-based therapy and recognize p44/42 MAPK pathway as potentially involved in combination outcome.